They also crossed the internal border: travelers and captives in 19th century Argentina - Pérez Gras, María Laura (Revista Melibea, 2025)
There are few texts that give rise to the voices of female historical travelers and captives who narrated the crossing of the internal border in Argentine territory with the original communities during the nineteenth century. On the contrary, the official literature of the conquest of the "desert" reflects an ideology on the issues of gender and otherness in the terms chosen for the narration of this "national epic": Colonial imaginary spaces were metaphorically described in masculine erotic fantasies: penetration, rape, naked and available women (Szurmuk 2007: 85). In addition to recovering the transgressive look of Lucio V. Mansilla in Una excursión a los indios ranqueles (1870), where he includes testimonies of female captives and excaptives, we will take two texts that we consider essential in the rescue of narratives of women who crossed the internal border during the nineteenth century: Across Patagonia, by Florence Dixie, published in London, in 1880, and La cautiva o Rayhuemy, written by Father Lino Carbajal from the autobiographical account of Francisca Nieves Rosa de Valenzuela, which was collected, annotated and published, only in 1995, by the historian María Elena Ginobili de Tumminello, in Bahía Blanca.